Modern Sales Technologies and the Concept of Omni-Channel Sales in Food Retail Chains in Poland - Agnieszka BUDZIEWICZ-GUŹLECKA; Mariusz WOŹNIAKOWSKI (Communications of International Proceedings, 2021)
Retail chains have been investing in the search for and implementation of new tools supporting the retail process. Digital solutions prevail, including their use in traditional distribution channels. Such changes are part of the omni-channel concept. The article attempts to identify omni-channel sales in the food retail chains operating in Poland. Firstly, the article describes the substance of modern communication technologies and the omni-channel sales. A particular emphasis is put on the most developed omni-channel concept based on the study of the literature. Secondly, the article includes a market analysis and the use of modern tools that that fit into the omni-channel concept. Finally, the analysis shows to what extent the current food retail chains in Poland have been using selected omni-channel solutions and indicates the direction of further changes.
Keywords: Modern Technologies; E-Commerce; Omni-Channel; Retail.